The Breastfeeding Experiences of Older First-Time Mothers: A Constructivist Grounded Theory Study - Edwards, Rosann (Université d'Ottawa / University of Ottawa, 2019)
Background: In Canada over the past three decades first-time mothers > 35 years have been, and continue to be, the fastest growing demographic of new mothers. The quality of a mother’s breastfeeding experience has the potential to affect breastfeeding duration and other mothering behaviours that promote healthy maternal-infant attachment, optimal infant growth and development, and maternal mental health. Previous studies on breastfeeding have not examined the breastfeeding experiences of older first-time mothers. Older mothers are a group that is potentially unique due to their experience of coming to motherhood in the context of the growing phenomenon of delayed childbearing in the 21st century. Older women often come to motherhood with both well-established life and professional experiences, and as such may have different needs from those of their younger or multiparous counterparts. Research Question: What factors affect how first-time mothers >35 years of age make decisions about breastfeeding, and how do these factors affect the decisions they make related to breastfeeding in the first six months postpartum? Design: A constructivist grounded theory study Findings: The theory of From Ideology to Independence: Older First-time Mothers, Breastfeeding, and Becoming a Mother provides an explanation of both the factors affecting the decisions the mothers made related to breastfeeding, and how these factors affected the decisions they ultimately made. The mothers worked through the processes of learning breastfeeding, redefining self, and defining motherhood. This occurred under the belief that breastfeeding is pivotal to motherhood. Over the first six months postpartum, the influence of the belief in breastfeeding defining mothering waned as the mothers became increasingly active agents in decision making around infant feeding and their overall mothering practices.
Keywords: Breastfeeding; Older Mothers